The financial budget of professional sports clubs as one of the requirements for the success of sports professionalism in Algeria - Hachrouf, oussama; Ladjal, yahia (sports creativity, 2025)
The study aimed to know the role of the financial budget of professional sports clubs as one of the requirements for the success of sports professionalism in Algeria, and to reach the results was used descriptive analytical method on a sample consisting of 30 members of the board of directors of clubs who represent 10 professional sports clubs They are active in the first and second professional association selected in a random way, and for the members of the board of directors is selected in a deliberate way, and we used the questionnaire tool, where the results indicated that the financial balance of professional sports clubs is considered as one of the requirements for the success of professional sports In Algeria